2018
DOI: 10.1186/s13630-018-0060-5
|View full text |Cite
|
Sign up to set email alerts
|

Glioma cell proliferation is enhanced in the presence of tumor-derived cilia vesicles

Abstract: BackgroundThe mechanisms by which primary cilia affect glioma pathogenesis are unclear. Depending on the glioma cell line, primary cilia can promote or inhibit tumor development. Here, we used piggyBac-mediated transgenesis to generate patient-derived glioblastoma (GBM) cell lines that stably express Arl13b:GFP in their cilia. This allowed us to visualize and analyze the behavior of cilia and ciliated cells during live GBM cell proliferation.ResultsTime-lapse imaging of Arl13b:GFP+ cilia revealed their dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 61 publications
(91 reference statements)
6
52
0
Order By: Relevance
“…increased SMO accumulation) in cells with a loss‐of‐function mutation in Arl13b . However, in cancer cells, Arl13b promotes the ciliary localisation of SMO, although this difference may be explained by the transformed state of these cells . One scenario to explain our observations is that Rab35 principally targets Arl13b, possibly as a direct effector or a more distant upstream regulator.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…increased SMO accumulation) in cells with a loss‐of‐function mutation in Arl13b . However, in cancer cells, Arl13b promotes the ciliary localisation of SMO, although this difference may be explained by the transformed state of these cells . One scenario to explain our observations is that Rab35 principally targets Arl13b, possibly as a direct effector or a more distant upstream regulator.…”
Section: Discussionmentioning
confidence: 75%
“…Alternatively, Rab35 could regulate membrane diffusion barriers at the transition zone that keep Arl13b in the cilium [88,112,113]. Another possibility is that ciliary Rab35 controls Arl13b localisation and cilium structure by regulating ectosomes that bud from ciliary membranes to control their composition and length [20][21][22][23][24]114]; indeed, some ciliary ectosomes are Arl13b-positive [108]. However, this model is mitigated A Model of how activated (GTP-bound) Rab35 at the ciliary and/or periciliary (pocket) membrane limits Arl13b ciliary levels.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, TLQP-21 and C3aSA induced almost identical transcriptomic changes, with upregulation of most of the DEGs, many of which are associated with cellular movement and proliferation. They include Arl13b, which is involved in cell projection and primary cilia formation [75,76]. Dpysl2 encodes a member of the collapsing response mediator protein family (CRMP2) facilitating growth, guidance or polarity by having functions related to the cytoskeletal dynamics [77].…”
Section: Discussionmentioning
confidence: 99%
“…Live imaging has revealed that cilia are dynamic organelles that shed ciliary vesicles in a phenomenon called cilia excision or decapitation. The release of ciliary vesicles is involved in the control of cell proliferation, cilia disassembly, and ciliary signaling (36)(37)(38)(39). For example, when ciliary trafficking is perturbed, as in BBsome mutants, the rate of cilia excision increases as a mechanism to release the excess of GPCRs and prevent their accumulation in the axoneme (36).…”
Section: Discussionmentioning
confidence: 99%
“…The ciliary tip is also a site of ectocytosis, a process by which vesicles are shed from the cilium. This process is linked to signaling from primary cilia and proper regulation of ectocytosis is important for controlling the ciliary length and for maintaining the stability of cilia (35)(36)(37)(38)(39). To test whether ciliary scission and ectocytosis could be affected in Csnk2a1-depleted cells leading to ciliary instability, we purified extracellular vesicles (EVs), that included cilia shedding through scission from supernatants collected from the culture media of control and Csnk2a1-mutant cells.…”
Section: Csnk2a1 Is Required For Cilium Stabilitymentioning
confidence: 99%